2015
DOI: 10.1016/j.bbadis.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 gene transfer reverses body weight gain and fatty liver in obese mice

Abstract: Interleukin-6 (IL-6) is a multifunctional protein and has a major influence on energy metabolism. The current study was designed to assess the therapeutic effect of overexpression of Il-6 gene through gene transfer on high fat diet-induced obese mice. Hydrodynamic delivery of 1 μg pLIVE-IL6 plasmid per mouse into C57BL/6 obese mice resulted in peak level at 10 ng/ml of circulating IL-6 1 day after gene transfer and above 1n g/ml thereafter for a period of 6 weeks. Persistent Il-6 gene expression did not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 41 publications
4
59
0
Order By: Relevance
“…T cells) and non-immune cells, mainly adipose tissue and skeletal muscle [60] . IL-6 acts on a wide range of tissues through the modulation of cell growth and differentiation [60] .…”
Section: Il-6mentioning
confidence: 99%
See 2 more Smart Citations
“…T cells) and non-immune cells, mainly adipose tissue and skeletal muscle [60] . IL-6 acts on a wide range of tissues through the modulation of cell growth and differentiation [60] .…”
Section: Il-6mentioning
confidence: 99%
“…T cells) and non-immune cells, mainly adipose tissue and skeletal muscle [60] . IL-6 acts on a wide range of tissues through the modulation of cell growth and differentiation [60] . For instance, in WAT, IL-6 increases lipolysis [61] , whereas in skeletal muscle, it increases glycolysis and improves insulin sensibility [62] .…”
Section: Il-6mentioning
confidence: 99%
See 1 more Smart Citation
“…Il-6 could also control the lipid accumulation [42] and its reduction after 8 weeks of HC diet appears to imply in more triglycerides in the liver. Moreover, this cytokines was already described to have an anti-inflammatory response [43].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…On the other hand, another important inflammatory factor in NAFLD patients is the tumor necrosis factor (TNF-). Researchers have demonstrated that the severity of NAFLD might be associated with the increased level of TNF- in NAFLD patients (29,30). TNF could bind to trimerized TNF receptor type I and activate NF-B via the inhibitor of the nuclear factor kappa-B kinase (IKK) pathway.…”
Section: Ppar Agonists and Inflammation In Nafldmentioning
confidence: 99%